TMEM16A and Myocardin Form a Positive Feedback Loop That Is Disrupted by KLF5 During Ang II–Induced Vascular Remodeling. Issue 2 (August 2015) - Zhang, Xin-hua; Zheng, Bin; Yang, Zhan; He, Ming; Yue, Ling-yan; Zhang, Ruo-nan; Zhang, Ming; Zhang, Wei; Zhang, Xuan; Wen, Jin-kun
Abstract : The TMEM16A protein is an important component of Ca 2+ -dependent Cl − channels (CaCCs) in vascular smooth muscle cells. A recent study showed that TMEM16A inhibits angiotensin II–induced proliferation in rat basilar smooth muscle cells. However, whether and how TMEM16A is involved in vascular remodeling characterized by vascular smooth muscle cell proliferation remains largely unclear. In this study, luciferase reporter, Western blotting, and qRT-PCR assays were performed. The results suggested that myocardin promotes TMEM16A expression by forming a complex with serum response factor (SRF) on the TMEM16A promoter in human aortic smooth muscle cells (HASMCs). In turn, upregulated TMEM16A promotes expression of myocardin and vascular smooth muscle cell marker genes, thus forming a positive feedback loop that induces cell differentiation and inhibits cell proliferation. Angiotensin II inhibits TMEM16A expression via Krüppel-like factor 5 (KLF5) in cultured HASMCs. Moreover, in vivo experiments show that infusion of angiotensin II into mice causes a marked reduction in TMEM16A expression and vascular remodeling, and angiotensin II–induced effects are largely reversed in KLF5 null (KLF5 −/− ) mice. KLF5 competes with SRF to interact with myocardin, thereby limiting myocardin binding to SRF and the synergistic activation of the TMEM16A promoter by myocardin and SRF. Our studies demonstrated that angiotensin II induces KLF5 expression and facilitates KLF5 association with myocardin to disrupt the myocardin–SRF complex, subsequently leading to inhibition of TMEM16A transcription. Blocking the positive feedback loop between myocardin and TMEM16A may be a novel therapeutic approach for vascular remodeling. Abstract : Supplemental Digital Content is available in the text.